Effect of non-thermal atmospheric pressure plasma on MDA-MB-231 breast cancer cells - Ramin Mehrabifard; Hassan Mehdian; mahdi bakhshzadmahmodi (Mazandaran University of Medical Sciences, 2017)
Cold atmospheric plasma (CAP) has received great attention due to its noteworthy ability, and has also been widely studied over few decades in physics, biology and medicine. The purpose of this study is to evaluate the cold atmospheric pressure plasma effects on the proliferation of breast cancer cells. MDA-MB-231 was used for this experiment. MDA-MB-231 cells were cultured in 24-well plate and treated with non-thermal plasma. The viability of the cancer cells was determined by MTT assay. Different input power was applied in this experience (20-35W), and treatment time was between 5s and 25s. For reducing thermal damage, gas temperature was less than 37 ˚C. The Viability of breast cancer cells was significantly decreased after plasma treatment. The results showed that viability was decreased with an increment of plasma power and plasma exposure time. These results suggest that non-thermal atmospheric pressure plasma could strongly have cytotoxicity effect on cancerous breast cell.